Semiotic engineering : A new paradigm for designing interactive systems - Souza, Clarisse Sieckenius de (2006)
This paper presents semiotic engineering – a semiotic theory of HCI. The theory has the advantage to integrate back end and front end design and development perspectives into a single metacommunication process that affects the user’s experience and, ultimately, the success of any system. By means of illustrative examples, we show the kinds of effects that can be achieved with the theory, and discuss why a semiotic perspective is relevant for the future of information systems